Preparation and magnetic characterization of Fe/metal oxide nanocomposite particles by means of hydrogen reduction assisted ultrasonic spray pyrolysis (USP-HR) - Ebin, Burcak; Toparlı, Çiğdem; Gürmen, Sebahattin (Walter de Gruyter GmbH, 2013)
Abstract Fe/metal oxide nanocomposite particles were produced by means of hydrogen reduction assisted ultrasonic spray pyrolysis. Fe/Fe0.761Mg0.239O and Fe/MgO nanocomposite particles were obtained at 600 and 800 °C, respectively. The thermodynamics of the formation reactions were investigated. Increasing the reaction temperature allowed efficient reduction of the precursor to metallic iron that induces the formation of pure MgO phase. The crystallite sizes of the Fe in the composite structures slightly increased, and also the crystallite sizes of the oxides decreased with elevating temperature. The nanocomposite particles exhibited spherical morphology and their particle sizes were slightly different. All of the samples showed ferromagnetic characteristics and the results indicate that the amount of metal and metal oxide phases most affected the saturation magnetizations of the composite particles which were lower than pure iron.